(untitled) - Betsis, Andrew (Thành phố Hồ Chí Minh, 2014)
The Tests have been designed to provide students with the strategies they need, in order to familiarize themselves with the FORMAT of the 7 TOEIC exam tasks. Bilingual Glossaries for various languages are available. A set of 7 Audio CDs presented in the exact format of the exam is also vailable
Keywords: English language,Tiếng Anh